2010
DOI: 10.1007/s11144-010-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Chiral vanadyl salen catalyst immobilized on mesoporous silica as support for asymmetric oxidation of sulfides to sulfoxides

Abstract: cThe chiral vanadyl salen complex was immobilized into mesoporous silica by a covalent grafting method using 3-aminopropyltriethoxysilane as a reactive surface modifier. The formation and integrity of the complex have been confirmed by FT-IR, UV-vis and BET measurements and the complex was tested in the asymmetric oxidation of sulfide to sulfoxide using H 2 O 2 as oxidant. The immobilized complex showed better catalytic activity than the neat complex, while the neat complex has deactivated in the reaction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The C‐N stretching frequency is present in the region 1350–1410 cm −1 in the spectra of Fe 3 O 4 @S‐ABENZ and fe3o4@s‐abenz@VO. A characteristic band due to the C═C stretching frequency appears as a strong band at 1600 cm −1 in Fe 3 O 4 @S‐ABENZ and fe3o4@s‐abenz@VO spectra . The characteristic V═O stretching frequency in the Fe 3 O 4 @S‐ABENZ@VO spectrum appears at 995 cm −1 , within the range of 970–997 cm −1 reported for similar oxovanadium(IV) complexes …”
Section: Resultssupporting
confidence: 76%
“…The C‐N stretching frequency is present in the region 1350–1410 cm −1 in the spectra of Fe 3 O 4 @S‐ABENZ and fe3o4@s‐abenz@VO. A characteristic band due to the C═C stretching frequency appears as a strong band at 1600 cm −1 in Fe 3 O 4 @S‐ABENZ and fe3o4@s‐abenz@VO spectra . The characteristic V═O stretching frequency in the Fe 3 O 4 @S‐ABENZ@VO spectrum appears at 995 cm −1 , within the range of 970–997 cm −1 reported for similar oxovanadium(IV) complexes …”
Section: Resultssupporting
confidence: 76%
“…Oxovanadium(IV) complexes of Schiff bases are now established as an important class of drugs because of their medical importance due to their insulin-like effect (Thompson et al, 1999). Additionally, these complexes are used in some chemical processes as catalysts (Ben Zid et al, 2010), and also as biological models in understanding the structure of biomolecular and biological processes (Meshkini & Yazdanparast, 2010). Furthermore, vanadium compounds are interesting because of their adverse effect on the hydroprocessing catalysts used in refining crude oil (Bu et al, 1996).…”
Section: Commentmentioning
confidence: 99%
“…There is an extensive literature on their application in some important industrial and life processes (Chang et al, 1997;Mohammadi & Yazdanparast, 2009;Boghaei et al, 2006). They are interesting because of their antitumour and antiviral properties (Meshkini & Yazdanparast, 2010;Rehder, 2003); it was also demonstrated that they can show antioxidant activity (Mohammadi & Yazdanparast, 2010) and be applied as catalysts (Ben Zid et al, 2010). The oxide group of oxovanadium complexes has taken part in a number of oxide-transfer reactions (Adã o et al, 2009).…”
Section: Commentmentioning
confidence: 99%